1992
DOI: 10.1021/j100188a031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sensitizer heavy atoms on singlet oxygen generation efficiency

Abstract: 3723this correlation. The data points, plotted as k!s/k:,, are compared with the predicted behavior of eq 7 (solid line). Also shown in this figure is the hard-sphere rate constant, represented by the dashed line of zero slope and intercept one. This plot illustrates graphically our observation made earlier that the rotational relaxation proceeds more efficiently than the hard-sphere rate constant since all data p i n t s lie below the dashed line. It is also shown in Figure 9 that the measured rate constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 4 publications
3
36
0
Order By: Relevance
“…The T-T absorption spectrum and ketyl radical absorption spectrum overlap strongly, as in the cases of benzophenone, biacetyl, and camphr~quinone. '~ The hT value for benzil in ethanol took into account the ketyl radical buildup (see, for example, ref 12).…”
Section: Methodsmentioning
confidence: 99%
“…The T-T absorption spectrum and ketyl radical absorption spectrum overlap strongly, as in the cases of benzophenone, biacetyl, and camphr~quinone. '~ The hT value for benzil in ethanol took into account the ketyl radical buildup (see, for example, ref 12).…”
Section: Methodsmentioning
confidence: 99%
“…Together with eq 7 this yields the expressions for P I and P3: (9) For kd the value k: = 3.2 X 1Olo M-I s-l found for oxygen quenching of the SI state of CHR will be used in the following evaluations.…”
Section: P I + 3p3mentioning
confidence: 99%
“…This effect is generally achieved by the introduction of heavy atoms into the molecular structure, resulting in spin‐orbit perturbation. [ ] Nevertheless, different authors [ ] have recently suggested the development of a new generation of PDT photosensitizers, which can absorb two photons simultaneously in the same quantum event (TPA). The main feature of two‐photon absorbing photosensitizers is that they show higher tissue penetration and photons with half energy with respect to the corresponding one‐photon transition can be used.…”
Section: Introductionmentioning
confidence: 99%